Water potential and gas exchanges in sugarcane irrigated with saline waters - Raquele M. de Lira; Ênio F. de F. e Silva; Marcone da S. Barros; Leandro C. Gordin; Lilia G. Willadino; Rodrigo F. Barbosa (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT In Pernambuco, state in the northeastern region of Brazil, in the coastal areas, due to the intrusion of seawater, the waters used for sugarcane irrigation can have high salt contents and cause serious problems to soil and plant. The present study aimed to evaluate the effects of irrigation with saline water on the physiology of sugarcane, variety RB867515, irrigated under five salinity levels of 0.5; 2.0; 3.5; 5.0 and 6.5 dS m-1 in a completely randomized design, with four replicates in drainage lysimeters. The study was conducted in the period from December 2014 to June 2015, at the Federal Rural University of Pernambuco (UFRPE). Salinity levels were obtained by dissolving NaCl and CaCl2 in water from the local supply system (ECw = 0.5 dS m-1). Leaves were analyzed for stomatal conductance, transpiration and photosynthesis at 140, 229 and 320 days after planting (DAP) and for water potential at 137, 243 and 318 DAP. Increase in irrigation water salinity inhibited all variables at the respective plant ages and with greater intensity in the first evaluations (140 and 229 DAP) for stomatal conductance and transpiration. Photosynthesis and water potential showed the greatest linear reductions at the last data collection (320 and 318 DAP), respectively. Increase in salinity of irrigation water hampered water potential and gas exchange in the leaves of RB867515 sugarcane.